2012
DOI: 10.1111/j.1365-2516.2012.02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the interaction between anti‐FVIII antibodies and FVIII from therapeutic concentrates, with and without von Willebrand factor, assessed by surface plasmon resonance

Abstract: The presence of VWF in plasma-derived FVIII (pdFVIII/VWF) products has been pointed out as a key difference with recombinant FVIII (rFVIII) products with regard to immunogenicity. A Surface Plasmon Resonance (SPR) study was designed to characterize in detail the interaction between anti-FVIII (IgGs) from a severe haemophilia A patient, and FVIII from concentrates of different sources. Full-length rFVIII (preincubated or not with purified VWF), B domain-deleted (BDD)-rFVIII and pdFVIII/VWF were analysed. To ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Our ex vivo studies demonstrated, for the first time in the clinical setting, that plasma from patients who received pdFVIII/VWF consistently showed less inhibitory reactivity regardless of the type of rFVIII product they received. Previous studies performed in vitro on different FVIII‐containing products have shown that the rFVIII concentrates invariably contained a fraction of factor FVIII related antigen (FVIII:Ag) molecules (approximately 20%) which was unable to associate with VWF 28,29 . Results of the present clinically oriented ex vivo study confirmed a high level of correspondence with those of previous in vitro studies 14,30 (refer to Supporting information for indirect comparisons).…”
Section: Discussionsupporting
confidence: 86%
“…Our ex vivo studies demonstrated, for the first time in the clinical setting, that plasma from patients who received pdFVIII/VWF consistently showed less inhibitory reactivity regardless of the type of rFVIII product they received. Previous studies performed in vitro on different FVIII‐containing products have shown that the rFVIII concentrates invariably contained a fraction of factor FVIII related antigen (FVIII:Ag) molecules (approximately 20%) which was unable to associate with VWF 28,29 . Results of the present clinically oriented ex vivo study confirmed a high level of correspondence with those of previous in vitro studies 14,30 (refer to Supporting information for indirect comparisons).…”
Section: Discussionsupporting
confidence: 86%
“…A recent study used surface plasmon resonance to characterize the interaction between human anti‐FVIII IgG inhibitors and FVIII in concentrates from different sources . Although measuring an antigen–antibody interaction by surface plasmon resonance is a complex process, it has a strong validation method.…”
Section: Evidence From a Surface Plasmon Resonance Studymentioning
confidence: 99%
“…rFVIII , recombinant FVIII; BDD rFVIII , B domain deleted rFVIII ; rFVIII /VWF, rFVIII incubated with von Willebrand factor (VWF); pdFVIII/VWF, plasma‐derived FVIII containing VWF. Adapted from .…”
Section: Evidence From a Surface Plasmon Resonance Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The high purity concentrates are manufactured using monoclonal antibodies to factor VIII or vWF. These products underwent multiple purification steps including heat treatment to reduce risk of viral transmission [20]. It was revealed in the 1990s, that one lot of pdFVIIIC to be associated with high risk of appearance of factor VIII inhibitor in patients who were extensively under infusion of pdFVIIIC.…”
Section: Plasma Derived Factor VIII Concentrates (Pdfviiic)mentioning
confidence: 99%